Activation of Kupffer cells in NAFLD and NASH: mechanisms and therapeutic interventions - Xu, Gao-Xin; Wei, Song; Yu, Chao; Zhao, Si-Qi; Yang, Wei-Jun; Feng, Yong-Heng; Pan, Chao; Yang, Kun-Xing; Ma, Yong (Frontiers in Cell and Developmental Biology, 2023)
Non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) are emerging as the leading causes of liver disease worldwide. These conditions can lead to cirrhosis, liver cancer, liver failure, and other related ailments. At present, liver transplantation remains the sole treatment option for end-stage NASH, leading to a rapidly growing socioeconomic burden. Kupffer cells (KCs) are a dominant population of macrophages that reside in the liver, playing a crucial role in innate immunity. Their primary function includes phagocytosing exogenous substances, presenting antigens, and triggering immune responses. Moreover, they interact with other liver cells during the pathogenesis of NAFLD, and this crosstalk may either delay or exacerbate disease progression. Stimulation by endogenous signals triggers the activation of KCs, resulting in the expression of various inflammatory factors and chemokines, such as NLRP3, TNF-α, IL-1B, and IL-6, and contributing to the inflammatory cascade. In the past 5 years, significant advances have been made in understanding the biological properties and immune functions of KCs in NAFLD, including their interactions with tissue molecules, underlying molecular mechanisms, signaling pathways, and relevant therapeutic interventions. Having a comprehensive understanding of these mechanisms and characteristics can have enormous potential in guiding future strategies for the prevention and treatment of NAFLD.